2013
DOI: 10.1002/ccd.24736
|View full text |Cite
|
Sign up to set email alerts
|

Experience using the new GORE® septal occluder at the margins

Abstract: Complex atrial anatomy continues to challenge transcatheter device closure of septal defects. Devices and technology continue to evolve. We report three cases from our institution where the new Gore Septal Occluder was utilized for the closure of a lateral tunnel fenestration, a moderate-sized secundum atrial septal defect and a long tunnel patent foramen ovale. Each case highlights the successful use of this new generation device in challenging circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…In the face of 3 patients (7.3%) experiencing either device thrombus formation or new onset paroxysmal atrial fibrillation in our study, the combination of oral anticoagulation (coumadine, target INR 2.0–3.0) in addition to anti‐platelet therapy with aspirin 100 mg daily for 3 months after device implantation could be a reasonable concept for future routine prophylaxis after interventional PFO closure. Notably, this approach should be discussed irrespective of the applied closure device as comparable occurrence rates of new onset atrial arrhythmia and thrombus formation were observed both with the Gore® Septal Occluder as well as with other closure devices used in RCTs (GSO 4.1% vs. other devices in RCTs 4.7%) …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the face of 3 patients (7.3%) experiencing either device thrombus formation or new onset paroxysmal atrial fibrillation in our study, the combination of oral anticoagulation (coumadine, target INR 2.0–3.0) in addition to anti‐platelet therapy with aspirin 100 mg daily for 3 months after device implantation could be a reasonable concept for future routine prophylaxis after interventional PFO closure. Notably, this approach should be discussed irrespective of the applied closure device as comparable occurrence rates of new onset atrial arrhythmia and thrombus formation were observed both with the Gore® Septal Occluder as well as with other closure devices used in RCTs (GSO 4.1% vs. other devices in RCTs 4.7%) …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a dedicated device allowing safe, complete and rapid defect closure especially in those challenging PFO anatomies is desirable. The Gore ® Septal Occluder has already proven low periprocedural risk, high successful implantation rates and good closure rates at short‐term follow‐up examination in a number of previous studies . However, patients enrolled in these trials were mainly presenting with “ordinary” PFO anatomies (ASA 194/589; 32.9%; long tunnel 91/339; 26.8%, tunnel length data of 250 patients enrolled in 4 trials are missing .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations